The Impact of Psychological Health on Patient Recovery After Arthroplasty - Zhang, Zhen; Xing, Qiqi; Zhong, Da; Pan, Yixiao; He, Tailai; Hu, Yihe; Wang, Long (Frontiers in Psychiatry, 2022)
Purpose: The purpose of this study was to determine the relationship between psychological health and postoperative recovery and satisfaction in patients undergoing total joint arthroplasty (TJA). Methods: We prospectively enrolled patients undergoing TJA from July 2019 to December 2020. A psychological evaluation was conducted according to the Hospital Anxiety and Depression Scale (HADS). Based on the preoperative HADS scores, we grouped the patients into two groups: the symptomatic group and the asymptomatic group. Data on the Harris Hip Score (HHS), Knee Society Knee Scoring System (KSS), Forgotten Joint Score-12 (FJS-12), Short Form-12 (SF-12) and Numeric Rating Scale (NRS) for pain in these two groups were collected preoperatively and postoperatively. Then, these data were analyzed by Statistical Package for Social Sciences (SPSS) version 19. Results: The final cohort consisted of 80 patients. Patients undergoing TJA had significantly decreased HADS and NRS scores and improved HHS, KSS, SF-12, and FJS-12 scores (all p<0.001). Compared with the symptomatic group, the asymptomatic group showed better postoperative recovery (p<0.05), especially after total knee arthroplasty (TKA) (p<0.05). Good postoperative recovery positively impacted the patients’ postoperative psychological state. Conclusions: In conclusion, psychological state can affect recovery after TJA, and successful TJA can help improve patients’ psychological states, especially after TKA.